Assemblage-democracy: Reconceptualising democracy through material resource governance. (June 2021) - Eadson, Will; Van Veelen, Bregje
Abstract: This article furthers political geographic thinking on democracy by generating and employing a conceptualisation of 'assemblage-democracy'. Bringing an assemblage perspective to democratic thinking brings to the fore three key dimensions: the co-constitution of material and non-material connections; connectivity and associations, in particular engagement with multiple heterogeneous 'minoritarian' publics; and the (re)construction of spatial configurations such as scale. We employ these three dimensions of materiality, publics, and scale, in combination with the concept of (de)territorialisation to produce a geographic conceptualisation of democracy as emergent, precarious, and plural. We operationalise and refine the concept of assemblage-democracy through an empirical analysis of democratic experiments with energy resources. Specifically, we analyse negotiations involved in emergent democratic energy experiments through in-depth qualitative empirical study of community-owned energy projects in the UK, asking what kind of democracy emerges with new technologies and how? In answering this question, we demonstrate the fragile, contingent, and contested nature of democratic practices and connections produced in the (re)enactment of energy infrastructures. In doing so, this article also shows how an assemblage lens can offer a renewed understanding of how democratic politics is configured through material resource governance.